Financial information for management - ACCA (Feltham Foulks Lynch, 2002)
A study text designed for part 1 of the 2001 ACCA professional examinations in accountancy. The texts combine focus on the exam, clear format and useful learning tools and take full account of topics in the ACCA's syllabus.